Kualitas Kinerja Reproduksi Induk Ikan Guppy Albino Full Platinum (Poecilia reticulata) Yang diberi Tepung Taoge (Bean sprouts) Dalam Pakan - Syahrizal Syahrizal; M Yusuf Arifin; Zezha Febriand (Universitas Batangahari Jambi, 2023)
This study aims to determine the level of addition of bean sprout flour in feed as vitamin E to help the reproductive system in rearing guppy fish (Poecilia reticulate). The design used was a Completely Randomized Design (CRD) with 4 treatments 3 replications, each treatment was: A. Without Sprout Flour 0% (SF 0%), B Sprout Flour 2% (SF 2.0%), C Sprout Flour 4% (SF 4.0%), D Sprout Flour 6% (SF 6,0%). The fish used in this study were female guppy fish measuring 0,38 – 0,51 gram. Growth of gonads for all treatments ranged from 0.61% - 0.68%, gonadal maturity index ranged from 0.61 –0.81 gram, number of pups born ranged from 10 – 23 per head, guppy birth duration ranged from 13 - 19 days, feed conversion ratio ranged from 2.53 - 2.89. The results of the analysis of the water quality of the rearing medium showed that the water quality was still in the proper range for the maintenance of guppy fish. The best reproductive performance and stress response to the addition of bean sprout flour to guppy fish feed (Poecilia reticulate) was treatment C (the addition of bean sprout flour was 4%).